Answer:
Cartesian Equation: y = √(1 - x^2)
Graph: Second one
Explanation:
x^2 = sin^2(θ/2),
y^2 = cos^2(θ/2),
According to that theory, by the circle equation, x^2 + y^2 = 1^2.
When θ = -π, x = sin(-π/2) = - 1, and y = cos(-π/2) = 0
When θ = π, x = sin(π/2) = 1, and y = cos(π/2) = 0
The radius is 1 in this case, (x^2 + y^2 = r^2 -> x^2 + y^2 = 1^2 -> x^2 + y^2 = 1) as the semicircle ranges from (- 1, 0) to (1,0). Therefore your graph is the second one;
When theta = 0, x = sin 0 = 0, and y = cos 0 = 1, so the semicircle passes through (0, 1). To determine the equation, let's simply isolate "y" in the equation x^2 + y^2 = 1^2,
In Cartesian form, the equation is y = √(1 - x^2)